Cepacia Causing Nosocomial Urinary Tract Infection in Children - Ki Wuk Lee; Sang Taek Lee; Heeyeon Cho (Korean Society of Pediatric Nephrology, 2015)
Purpose: Burkholderia cepacia is an aerobic, glucose-non-fermenting, gram-negative bacillus that mainly affects immunocompromised and hospitalized patients. Burkholderia cepacia has high levels of resistance to many antimicrobial agents, and therapeutic options are limited. The authors sought to analyze the incidence, clinical manifestation, risk factors, antimicrobial sensitivity and outcomes of B. cepacia urinary tract infection (UTI) in pediatric patients. Methods: Pediatric patients with urine culture-proven B. cepacia UTI between January 2000 and December 2014 at Samsung Medical Center, a tertiary referral hospital in Seoul, Republic of Korea, were included in a retrospective analysis of medical records. Results: Over 14 years, 14 patients (male-to-female ratio of 1:1) were diagnosed with B. cepacia UTI. Of 14 patients with UTI, 11 patients were admitted to the intensive care unit, and a bladder catheter was present in 9 patients when urine culture was positive for B. cepacia. Patients had multiple predisposing factors for UTI, including double-J catheter insertion (14.2%), vesico-ureteral reflux (28. 6%), congenital heart disease (28.6%), or malignancy (21.4%). Burkholderia cepacia isolates were sensitive to piperacillin-tazobactam and sulfamethoxazole-trimethoprim, and resistant to amikacin and colistin. Treatment with parenteral or oral antimicrobial agents including piperacillin-tazobactam, ceftazidime, meropenem, and sulfamethoxazole-trimethoprim resulted in complete recovery from UTI. Conclusion: Burkholderia cepacia may be a causative pathogen for nosocomial UTI in pediatric patients with predisposing factors, and appropriate selection of antimicrobial therapy is necessary because of high levels of resistance to empirical therapy, including aminoglycosides.